2000
DOI: 10.1592/phco.20.11.898.35262
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Activity of Hepatic CYP3A4 in Patients Infected with HIV

Abstract: Variability in hepatic activity of CYP3A4 in HIV-positive patients may be greater than in controls and may explain some between-subject variability in plasma concentrations of indinavir. However, clearance mechanisms for protease inhibitors are complex, and if it is important to assess systemic exposure, the ERMBT is not a substitute for direct measurement of plasma concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 42 publications
3
29
1
Order By: Relevance
“…In addition, CYP3A4 activity appears to be more variable in HIV-positive patients than in non-infected subjects. [243] Moreover, Lee et al demonstrated that AIDS patients with acute illnesses had altered patterns of drug metabolism. [244] Data collected from studies performed in healthy volunteers should thus be extrapolated carefully to HIVinfected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CYP3A4 activity appears to be more variable in HIV-positive patients than in non-infected subjects. [243] Moreover, Lee et al demonstrated that AIDS patients with acute illnesses had altered patterns of drug metabolism. [244] Data collected from studies performed in healthy volunteers should thus be extrapolated carefully to HIVinfected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CYP3A4, the enzyme responsible for the metabolism of all PIs and NNRTIs, shows marked interindividual variability (32,33). Moreover, its activity appears to be even more variable in HIV-positive patients than in noninfected subjects (34). Also, habits like intake of alcohol and cigarette smoking could possibly interfere with the metabolism of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison between the study by Saah et al and Gerber et al suggested that the total exposure, C min , and C max of IDV and RTV are lower in HIV-infected patients than in seronegative subjects (11,25). Slain et al observed greater variability in hepatic activity of CYP3A4 in HIV-positive patients compared to HIV-negative healthy controls, which may have contributed to these findings (26). In addition, Acosta et al found that protease inhibitor-naïve patients with undetectable HIV RNA who were started on a protease inhibitor regimen had statistically higher C 8h and AUC 0-8 values than similarly treated patients with detectable HIV RNA at baseline (3).…”
Section: Discussionmentioning
confidence: 95%